Analysis and research on development status of Sichuan power grid and clean energy. (November 2022) - Liu, Jiawei; Li, Ting; Tang, Quan; Wang, Yunling; Su, Yunche; Zhu, Ke
Abstract: This paper introduces the development of clean energy in Sichuan province and the work done by the company in serving the development of clean energy. It mainly includes vigorously building power transmission channels to meet the needs of clean energy consumption, strengthening power grid planning and construction, serving the rapid development of new energy, tapping the potential of power grid operation, increasing the space of clean energy consumption, adopting multiple measures simultaneously, flexible trading, and increasing the intensity of clean energy consumption. And to solve the current situation and difficulties, put forward relevant policies and suggestions. It mainly includes suggestions to promote the construction of Sichuan electric power transmission channel, to call on the state to establish a policy mechanism to ensure Sichuan clean energy transmission and absorption, to arrange the development scale and progress of natural gas distributed energy, new energy, and other power sources in a reasonable and orderly manner. It is suggested that the development scale and progress of various power sources such as natural gas distributed energy and new energy should be reasonably and orderly arranged.